Effects of Cultured Root and Soil Microbial Communities on the Disease of Nicotiana tabacum Caused by Phytophthora nicotianae - Liu, Tianbo; Xiao, Yunhua; Yin, Jian; Yi, Tuyong; Zhou, Zhicheng; Hsiang, Tom; Tang, Qianjun; Chen, Wu (Frontiers in Microbiology, 2020)
Background Black shank, caused by the oomycete pathogen Phytophthora nicotianae, is responsible for huge economic losses worldwide. Research has focused on biocontrol to prevent disease and to minimize the use of synthetic fungicides. Methods We explored and compared the efficacy of suppressive microflora cultured from soil and roots on the growth of P. nicotianae for controlling the incidence of black shank. Results We found that 31 microfloral communities, enriched from 40 root samples but only 18 microfloral communities from soil samples, were antagonistic to P. nicotianae. In the field experiment, the root functional microflora (RFM) showed a greater suppressiveness of black shank than the soil functional microflora (SFM), while both RFM and SFM altered diversity, composition, structure, and interaction of soil bacterial communities during plant growth. Although the inoculation of RFM onto roots significantly (p < 0.05) decreased microbial diversity, molecular ecological network analysis indicated more possible interactions among soil microbes, while an opposite trend was observed with SFM inoculation. Linear regression analysis revealed that diversity indices were negatively correlated with suppression on the black shank, suggesting that specific taxa (e.g., OTU_322 and OTU_6478) could colonize and be active during plant growth at the expense of microbial diversity. In addition, 18 functional strains, isolated and screened from 3 RMF (12 strains) and 3 SMF (6 strains), were identified as bacterial genera Acinetobacter (12), Enterobacter (1), Bacillus (1), Stenotrophomonas (2), and Citrobacter (2). Spearman’s ranked correlation tests revealed that relative abundances of some OTUs affiliated with genera Acinetobacter, Enterobacter, and Bacillus were significantly (p < 0.05) and positively correlated with the level of disease suppression. Conclusion Microfloral communities or key functional species isolated from plant roots might be more effective in controlling black shank than those from soil, and they may be developed for disease control.